MEMBANGUN KEBERSAMAAN DAN KESATUAN SEBAGAI TUBUH KRISTUS DI TENGAH-TENGAH PELAYANAN GEREJA DAN MASYARAKAT BERSAMA JEMAAT HKBP TAMPUBOLON RESORT TAMPUBOLON DISTRIK XI TOBA HASUNDUTAN - Pintor Marihot Sitanggang; Henri Warnek Siburian; Lintong Sitorus; Joki Manaek Manalu; Ferdinand Fernando Silaen; Musa Aprindo Sirait; Wellem Saputra Munthe; Josua Hutagalung (STAI Darul Qalam Tangerang, 2025)
Ecclesiologically, the church is understood not only as a building, but as a gathering of believers who fellowship together, building community and unity as the Body of Christ. We clearly believe that the church is the body of Christ, and as the body of Christ, the church is one in fellowship. The fact that the church is the body of Christ makes it, in essence, very important in the lives of believers. The church is a fellowship of believers as a community of the body of Christ who have received and live in God's salvation through faith in Jesus Christ. The church is the body of Christ, and at the same time it is also sent by Him to proclaim salvation in the world. In the implementation of Community Service at HKBP Tampubolon Resort Tampubolon District XI Toba Hasundutan, the spirit of building togetherness and unity as the Body of Christ in the midst of church and community service is the calling and soul of the implementation of this Community Service. Building and developing togetherness and unity as the Body of Christ for the development of the Kingdom of God and the glory of the Lord Jesus Christ, the King of the church.